Multi-center nationwide comparison of seven serology assays reveals a SARS-CoV-2 non-responding seronegative subpopulation - Oved, Kfir; Olmer, Liraz; Shemer-Avni, Yonat; Wolf, Tamar; Supino-Rosin, Lia; Prajgrod, George; Shenhar, Yotam; Payorsky, Irina; Cohen, Yuval; Kohn, Yishai; Indenbaum, Victoria; Lazar, Rachel; et al. (EClinicalMedicine, 2020)
An Israeli national taskforce performed a multi-center clinical and analytical validation of seven serology assays to determine their utility and limitations for SARS-CoV-2 diagnosis. Serology assays from Roche, Abbott, Diasorin, BioMerieux, Beckman-Coulter, Siemens, and an in-house RBD ELISA were included. Negative samples from 2391 individuals representative of the Israeli population, and 698 SARS-CoV-2 PCR positive patients, collected between March and May 2020, were analyzed Immunoassays sensitivities between 81.5%-89.4% and specificities between 97.7%-100% resulted in a profound impact on the expected Positive Predictive Value (PPV) in low (<15%) prevalence scenarios. No meaningful increase was detected in the false positive rate in children compared to adults. A positive correlation between disease severity and antibody titers, and no decrease in antibody titers in the first 8 weeks after PCR positivity was observed. We identified a subgroup of symptomatic SARS-CoV-2 positive patients (~5% of patients), who remained seronegative across a wide range of antigens, isotypes, and technologies. The commercially available automated immunoassays exhibit significant differences in performance and expected PPV in low prevalence scenarios. The low false-positivity rate in under 20′s suggests that cross-reactive immunity from previous CoV strains is unlikely to explain the milder disease course in children. Finding no decrease in antibody titers in the first 8 weeks is in contrast to some reports of short half-life for SARS-CoV-2 antibodies. The ~5% who were seronegative non-responders, using multiple assays in a population-wide manner, represents the proportion of patients that may be at risk for re-infection. Israel Ministry of Health.